ANALISIS PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI DI KELAS XI IPS SMAN JOGOROTO JOMBANG - Niken Prabandari (Jurnal Pendidikan Akuntansi (JPAK), 2013)
Teaching materials have an important role for teachers and students because teaching materials can improve effectively and efficiently the learning process. Teachers will have difficulty in increasing the effectiveness of learning when teaching materials are uncomplete. So were for students, in the absence of teaching materials students will have difficulty in learning. The purpose of this study is to (1) know the teaching materials used in learning accounting and the reason teachers use these materials in the learning process accounting and (2) determine the feasibility of accounting teaching materials used. Data collection techniques using the interview, check out the qualifications of teaching materials, and documentation then analyzed using the answers to make the study of the distribution table and answer reviewers' scores determine with the provisions set score. The results showed (1) Teaching materials used by teachers in teaching accounting is KLKPD because KLKPD compiled by Jombang regency MGMP so that the material being taught not deviate. (2) Instructional materials used in teaching accounting feasible used as teaching materials with a percentage of 74.09%. Key Word: Analysis, Instructional Materials, Accounting